Dispersion liquid

By adding specific cellulose ethers and nonionic surfactants to the dispersion of tetrafluoroethylene polymers, the problems of low dispersibility and poor operability of tetrafluoroethylene polymers in water were solved, and the dispersion was realized The high stability and excellent properties of the polymer layer.

CN119343402APending Publication Date: 2025-01-21AGC INC
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202380046235.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-10
Filing Date
2023-04-14
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The dispersion of tetrafluoroethylene-based polymer in water is low, which leads to the dispersion being prone to foaming and poor operability, and the surface of the formed polymer layer is prone to defects.

Method used

A dispersion containing tetrafluoroethylene polymer, specific cellulose ether, nonionic surfactant and water is used to suppress the formation of coarse particles by adjusting the average particle size, specific surface area and surfactant content of the particles. Improve dispersion stability and operability.

Benefits of technology

High stability and operability of the dispersion are achieved, and the formed polymer layer has excellent heat resistance, electrical properties and surface appearance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005180269310000091
    Figure BDA0005180269310000091
Patent Text Reader

Abstract

Provided is a dispersion liquid containing a tetrafluoroethylene-based polymer, which has excellent dispersion stability and workability, and which is capable of forming a molded article having excellent physical properties such as heat resistance and electrical characteristics (low linear expansion coefficient, low dielectric constant, and low dielectric loss tangent), and particularly having excellent surface appearance. A dispersion liquid containing tetrafluoroethylene polymer particles, a nonionic surfactant, a cellulose ether having a degree of substitution of 1.4 or more, and water.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a dispersion containing particles of a tetrafluoroethylene-based polymer. Background Art

[0002] In recent years, in order to cope with the high speed and high frequency of mobile communication devices such as mobile phones, the insulation layer of the printed circuit board of the communication device is required to have a material with a low dielectric constant and a low dielectric loss tangent, and tetrafluoroethylene polymers have attracted much attention. As a material for forming an insulation layer containing the polymer, a dispersion containing particles of tetrafluoroethylene polymers and a liquid dispersion medium is known. Patent Document 1 proposes an aqueous dispersion containing a specified amount of polytetrafluoroethylene having a volume average particle size of 1 to 50 μm after dispersion and a water-soluble thickener. Patent Document 2 proposes an aqueous dispersion containing particles of a tetrafluoroethylene polymer having a specific particle size range, a non-alkylphenol nonionic surfactant, and a specific acetylene glycol surfactant. Prior art literature Patent Literature

[0003] Patent Document 1: Japanese Patent Application Publication No. 2019-052211 Patent Document 2: International Publication No. 2022 / 054762 Summary of the invention Technical problem to be solved by the invention

[0004] Aqueous dispersions have the advantages of versatility of equipment required for their use and high selectivity of substrates to be coated, etc. However, tetrafluoroethylene polymers have low surface tension, so their particles have low dispersibility in water, and the dispersions are prone to foaming, and it is difficult to say that the operability of aqueous dispersions, such as fluidity, is sufficient when used for coating, etc. This problem tends to become particularly prominent when using tetrafluoroethylene polymer particles having an average particle size of 1 μm or more as in Patent Document 1 and when the content of the particles in the aqueous dispersion increases. In addition, defects are likely to occur on the surface of a molded product such as a polymer layer formed from the aqueous dispersion, which tends to impair its surface appearance. In addition, the aqueous dispersion proposed in Patent Document 2 also has room for improvement in its operability such as foaming suppression.

[0005] The present inventors have found that in a dispersion containing tetrafluoroethylene polymers, specific cellulose ethers, nonionic surfactants and water, the formation of coarse particles is suppressed, the dispersion stability is excellent, foaming is suppressed, and it is easy to operate. It is also found that for formed articles such as the polymer layer formed by the dispersion, the physical properties such as heat resistance and electrical properties (low linear expansion coefficient, low dielectric constant and low dielectric loss tangent) brought by the tetrafluoroethylene polymers are excellent, and particularly its surface appearance is excellent, thereby reaching the present invention. An object of the present invention is to provide a dispersion containing a tetrafluoroethylene polymer having excellent dispersion stability and handleability, which can be formed into a molded product having excellent physical properties such as heat resistance and electrical properties (low linear expansion coefficient, low dielectric constant and low dielectric loss tangent), especially excellent surface appearance. Solutions to technical problems

[0006] The present invention has the following aspects. [1] A dispersion comprising tetrafluoroethylene polymer particles, a nonionic surfactant, a cellulose ether having a degree of substitution of 1.4 or more, and water. [2] The dispersion according to [1], wherein the average particle size of the tetrafluoroethylene polymer particles is 1 μm or more and less than 10 μm, and the specific surface area is 1 to 25 m 2 / g. [3] The dispersion according to [1] or [2], wherein the content of the tetrafluoroethylene polymer particles exceeds 30% by mass. [4] The dispersion according to any one of [1] to [3], wherein the tetrafluoroethylene polymer is a tetrafluoroethylene polymer having a carbonyl group. [5] The dispersion according to any one of [1] to [4], wherein the main chain carbon number of the tetrafluoroethylene polymer is 6 There are 100 to 3000 carbonyl-containing groups. [6] The dispersion according to any one of [1] to [5], wherein the nonionic surfactant contains an alcohol surfactant having an HLB value of less than 10. [7] The dispersion according to any one of [1] to [6], wherein the nonionic surfactant contains a nonionic surfactant having an HLB value of 10 or more. [8] The dispersion according to any one of [1] to [7], wherein the nonionic surfactant comprises an alcohol surfactant having an HLB value of less than 10 and a silicone surfactant having an HLB value of 10 or more. [9] The dispersion according to any one of [1] to [8], wherein the content of the nonionic surfactant is 1 to 15% by mass relative to the content of the particles.

[10] The dispersion according to any one of [1] to [9], wherein the degree of substitution of the cellulose ether is 1.9 to 2.9.

[11] The dispersion according to any one of [1] to

[10] , wherein the cellulose ether is carboxyalkyl cellulose, hydroxyalkyl cellulose or hydroxyalkyl alkyl cellulose.

[12] The dispersion according to any one of [1] to

[11] , wherein the cellulose ether is hydroxyalkyl cellulose or hydroxyalkyl alkyl cellulose.

[13] The dispersion according to any one of [1] to

[12] , further comprising a monohydric alcohol having 1 to 6 carbon atoms.

[14] The dispersion according to any one of [1] to

[13] , further comprising at least one selected from an aromatic polymer and an inorganic filler.

[15] A method for producing a laminate, wherein the dispersion described in any one of [1] to

[14] is placed on the surface of a substrate and heated to form a polymer layer containing the tetrafluoroethylene polymer, thereby obtaining a laminate having a substrate layer composed of the substrate and the polymer layer in sequence. Effects of the Invention

[0007] According to the present invention, a dispersion having excellent dispersion stability and operability can be provided, wherein the dispersion can form a molded product such as a coating film (polymer layer) having excellent physical properties such as heat resistance and electrical properties (low linear expansion coefficient, low dielectric constant and low dielectric loss tangent) brought by a tetrafluoroethylene polymer, and particularly having excellent surface appearance. DETAILED DESCRIPTION

[0008] The following terms have the following meanings. The "average particle size (D50)" is the volume-based cumulative 50% diameter of particles or fillers obtained by the laser diffraction / scattering method. That is, the particle size distribution is measured by the laser diffraction / scattering method, and the cumulative curve is obtained with the total volume of the particle group as 100%, and the particle size at the point where the cumulative volume is 50% on the cumulative curve. The D50 of the particles or fillers is determined by dispersing the particles in water and analyzing the particles by a laser diffraction / scattering method using a laser diffraction / scattering particle size distribution analyzer (LA-920 analyzer manufactured by Horiba, Ltd.). The “average particle size (D90)” is a volume-based cumulative 90% diameter of particles obtained in the same manner as D50. The specific surface area of ​​particles or fillers is a value calculated by measuring particles using a gas adsorption (constant volume method) BET multipoint method, and is determined using NOVA4200e (manufactured by Quantachrome Instruments). The "melting temperature" is the temperature corresponding to the maximum of the melting peak of a polymer as measured by differential scanning calorimetry (DSC). The "glass transition temperature (Tg)" is a value measured by analyzing a polymer using a dynamic viscoelasticity measurement (DMA) method. The "viscosity" is determined by measuring the dispersion using a B-type viscometer at 25°C and a rotation speed of 30 rpm. The measurement was repeated three times, and the average of the three measured values ​​was taken. The "thixotropic ratio" is a value calculated by dividing the viscosity η1 of the dispersion measured at a rotation speed of 30 rpm by the viscosity η2 measured at a rotation speed of 60 rpm. Each viscosity measurement was repeated 3 times, and the average of the 3 measured values ​​was taken. The "surface tension" of a solvent or solution is a value measured by the Wilhelmy method at 25°C using a surface tension meter. The "HLB (Hydrophilic-Lipophilic Balance) value" of the nonionic surfactant is a value determined by the Griffin method and defined by the following calculation formula. HLB value = 20 x [sum of chemical formula weights of hydrophilic moieties] / molecular weight The "degree of substitution" of cellulose ether is also called the degree of etherification, which indicates the number of hydroxyl groups (average value) substituted by alkoxy groups among the three hydroxyl groups on the glucose ring of cellulose. Theoretically, the degree of substitution can have a value between 0 and 3. Generally speaking, the higher the degree of substitution, the more hydrophilic it is. The degree of substitution is obtained by converting the value measured by the degree of substitution analysis method of hydroxypropyl methylcellulose described in the 18th revised edition of the Japanese Pharmacopoeia. The "unit" in a polymer refers to an atomic group based on a monomer formed by polymerization of the monomer. The unit may be a unit directly formed by a polymerization reaction, or a unit obtained by converting a part of the unit into another structure by treating the polymer. Hereinafter, the unit based on monomer a is also referred to as "monomer a unit".

[0009] The dispersion of the present invention (hereinafter also referred to as "the present dispersion") contains particles (hereinafter also referred to as "F particles") of a tetrafluoroethylene polymer (hereinafter also referred to as "F polymer"), a nonionic surfactant, a cellulose ether having a degree of substitution of 1.4 or more, and water. The dispersion liquid has excellent dispersion stability and operability, and the formed products such as the coating film (polymer layer) formed from the dispersion liquid have excellent physical properties such as heat resistance and electrical properties (low linear expansion coefficient, low dielectric constant and low dielectric loss tangent) brought by the tetrafluoroethylene polymer, especially excellent surface appearance. In addition, in this specification, the so-called "excellent surface appearance" includes excellent surface smoothness such as "less surface roughness" or "no streaks, cracks or defects on the surface" and other excellent appearance observed by visual recognition or analysis equipment. The reason why the present dispersion liquid is excellent in dispersion stability, foaming is suppressed, and workability is excellent is not necessarily clear, but is considered to be as follows.

[0010] In an aqueous dispersion containing F particles and a nonionic surfactant, the nonionic surfactant is adsorbed on the surface of the F particles, thereby improving the dispersibility of the F particles in water. Such interactions generated by adsorption are considered to be in a state of equilibrium, and the non-adsorbed nonionic surfactant can also be considered to exist at the gas-liquid interface, etc. In other words, while the aqueous dispersion has improved stability through the action of the nonionic surfactant, it is in a state where foam is easily generated, and it can also be considered to be in a state where the F particles are easily aggregated or coarsened starting from the foam. In order to stably disperse the F particles with low surface tension in water, an excess of nonionic surfactant is required, but this not only makes it easy to form this state, but it also significantly reduces the surface tension of the dispersion itself, reduces liquid properties such as thixotropy, and also reduces the operability of the aqueous dispersion. The present dispersion contains a specific cellulose ether in addition to a nonionic surfactant and water. It is presumed that the specific cellulose ether plays a role in the fluidity of the present dispersion and the adsorption of the surfactant on the F particles, and is considered to achieve a high balance between the defoaming effect of the surfactant and the maintenance of liquid properties such as thixotropy, i.e., the so-called trade-off relationship. As a result, it is considered that the formation of coarse particles is suppressed, and the present dispersion having excellent dispersion stability, suppressed foaming, and easy handling can be obtained. This action mechanism is more remarkable when the present dispersion contains two specific surfactants or a monohydric alcohol having 1 to 6 carbon atoms described later, and when the F polymer has an oxygen-containing polar group.

[0011] The F polymer in the present invention is a polymer containing units (hereinafter also referred to as "TFE units") based on tetrafluoroethylene (hereinafter also referred to as "TFE"). The polymer F may be either heat-fusible or non-heat-fusible. Here, a heat-fusible polymer refers to a polymer having a temperature at which a melt flow rate is 1 to 1000 g / 10 minutes under a load of 49 N. A non-heat-fusible polymer refers to a polymer having no temperature at which a melt flow rate is 1 to 1000 g / 10 minutes under a load of 49 N. The melting temperature of the heat-melting polymer F is preferably 180°C or higher, more preferably 200°C or higher. In this case, the heat resistance of a molded product such as a coating film (polymer layer) formed from the present dispersion is likely to be excellent. The melting temperature of the polymer F is preferably 325°C or lower, more preferably 320°C or lower. From the viewpoint that the above-mentioned mechanism of action is more likely to be manifested, the melting temperature of the F polymer is preferably 180°C to 325°C, more preferably 200°C to 325°C, and even more preferably 200 to 320°C.

[0012] The glass transition temperature of the F polymer is preferably 50° C. or higher, more preferably 75° C. or higher. The glass transition temperature of the F polymer is preferably 150° C. or lower, more preferably 125° C. or lower. The fluorine content of the F polymer is preferably 70% by mass or more, more preferably 72 to 76% by mass. The surface tension of the F polymer is preferably 16 to 26 mN / m. The surface tension of the F polymer can be measured by placing a drop of a mixed solution for wetting tension test specified in JIS K6768 (produced by Wako Pure Chemical Industries, Ltd.) on a flat plate made of the F polymer.

[0013] The F polymer is preferably polytetrafluoroethylene (PTFE), a polymer containing TFE units and ethylene-based units (ETFE), a polymer containing TFE units and propylene-based units, a polymer containing TFE units and perfluoro(alkyl vinyl ether) (PAVE)-based units (PAVE units) (PFA), and a polymer containing TFE units and hexafluoropropylene-based units (FEP), more preferably PFA or FEP, and further preferably PFA. As the F polymer, one of these polymers may be used alone, or two or more thereof may be used in combination, and may further contain units based on other comonomers. The PTFE may, for example, be a low-molecular-weight PTFE or a modified PTFE. As PAVE, CF2=CFOCF3, CF2=CFOCF2CF3 or CF2=CFOCF2CF3 (hereinafter also referred to as "PPVE") is preferred, and PPVE is more preferred.

[0014] The F polymer preferably has an oxygen-containing polar group, more preferably has a hydroxyl-containing group or a carbonyl-containing group, and further preferably has a carbonyl-containing group. In this case, this dispersion is easily excellent in dispersion stability and operability. And, the formed objects such as the coating (polymer layer) formed by this dispersion are easily excellent in physical properties such as heat resistance, electrical characteristics (low linear expansion coefficient, low dielectric constant and low dielectric loss tangent) or its surface appearance. As the hydroxyl group-containing group, a group containing an alcoholic hydroxyl group is preferred, and -CF2CH2OH or -C(CF3)2OH is more preferred. As the carbonyl-containing group, preferred are carboxyl group, alkoxycarbonyl group, amide group, isocyanate group, carbamate group (-OC(O)NH2), acid anhydride residue (-C(O)OC(O)-), imide residue (-C(O)NHC(O)-, etc.) or carbonate group (-OC(O)O-), and more preferred is acid anhydride residue.

[0015] In the case where the F polymer has an oxygen-containing polar group, the number of oxygen-containing polar groups in the F polymer is 1×10 6The number of oxygen-containing polar groups in the F polymer is 10 to 5000, and more preferably 100 to 3000. In this case, the interaction between the F polymer and the nonionic surfactant, and between the F polymer and the cellulose ether reaches a balance, and the liquid properties of the dispersion are particularly easy to improve. Here, the number of oxygen-containing polar groups in the F polymer can be quantified by the composition of the polymer or the method described in International Publication No. 2020 / 145133.

[0016] The oxygen-containing polar group may be contained in the monomer-based unit in the F polymer, or may be contained in the terminal group of the F polymer main chain, and the former is preferred. As the latter, F polymers having oxygen-containing polar groups as terminal groups derived from polymerization initiators, chain transfer agents, etc., and F polymers obtained by plasma treatment or electrolysis off-line treatment of F polymers may be exemplified.

[0017] The F polymer is preferably a polymer having a carbonyl group containing a TFE unit and a PAVE unit, more preferably a polymer containing a TFE unit, a PAVE unit and a unit based on a monomer having a carbonyl group, and further preferably a polymer containing these units in an amount of 90 to 99 mol%, 0.99 to 9.97 mol%, and 0.01 to 3 mol% relative to all units. As a specific example of the F polymer, the polymer described in International Publication No. 2018 / 16644 can be cited. As the monomer having a carbonyl group, itaconic anhydride, citraconic anhydride or 5-norbornene-2,3-dicarboxylic anhydride (hereinafter also referred to as "NAH") is preferred, and NAH is more preferred.

[0018] In the present invention, the D50 of the F particles is preferably 1 μm or more and 10 μm or less. The F particles may be solid particles or non-hollow particles. The F particles may be secondary particles formed of nanometer-level microparticles. The D50 of the F particles is preferably 1.0 μm or more, more preferably 1.5 μm or more. The D50 of the F particles is preferably 6 μm or less, more preferably 5 μm or less. Furthermore, D90 of the F particles is preferably 8 μm or less, more preferably 6 μm or less. When D90 of the F particles is below the upper limit, the above-mentioned mechanism of action is more likely to be manifested, and the present dispersion having a small number of coarse particles is easily obtained.

[0019] The specific surface area of ​​the F particles is preferably 1 to 25 m 2 / g, more preferably 6 to 15 m 2 / g. In this case, this dispersion is easy in dispersion stability and operability. And, the formed articles such as the coating film (polymer layer) formed by this dispersion are easy to be excellent in physical properties such as heat resistance, electrical properties (low linear expansion coefficient, low dielectric constant and low dielectric loss tangent) or their surface appearance. When the specific surface area of ​​the F particles is within the above range, the surface of the F particles is easily wetted by water or a monohydric alcohol having 1 to 6 carbon atoms described later, and the agglomerates of the F particles are easily broken up, so that the above mechanism of action is more likely to manifest.

[0020] The F particles are particles containing an F polymer, and preferably consist of an F polymer. The F particles are more preferably particles of a hot-melt F polymer having an oxygen-containing polar group with a melting temperature of 200 to 325° C. In this case, the above-mentioned mechanism of action is more likely to be manifested, and aggregation of the F particles is also suppressed. The F particles may further comprise resins or inorganic compounds other than the F polymer, and may form a core-shell structure having the F polymer as the core and the resins or inorganic compounds other than the F polymer as the shell, or may form a core-shell structure having the F polymer as the shell and the resins or inorganic compounds other than the F polymer as the core. Here, examples of the resin other than the F polymer include aromatic polyester, polyamideimide, polyimide and maleimide, and examples of the inorganic compound include silicon dioxide and boron nitride.

[0021] The F particles may be used alone or in combination of two or more. In addition, the F particles can be mixed with particles of non-thermal-fusible tetrafluoroethylene polymers. As F particles, particles of heat-fusible F polymers with a melting temperature of 200 to 325°C are preferred, and particles of heat-fusible F polymers with oxygen-containing polar groups with a melting temperature of 200 to 325°C are more preferred. In addition, as particles of non-thermal-fusible tetrafluoroethylene polymers, particles of non-thermal-fusible PTFE are preferred. In this case, the agglomeration inhibition effect brought about by the particles of the heat-fusible F polymer and the retention effect brought about by the fibrillation of the non-thermal-fusible tetrafluoroethylene polymer reach a balance, and the dispersibility of this dispersion is easily improved. In addition, in the formed products such as the coating (polymer layer) formed therefrom, the electrical properties of the non-thermal-fusible tetrafluoroethylene polymer are easily highly manifested.

[0022] Examples of the nonionic surfactant contained in the present dispersion include glycol-based surfactants, acetylene-based surfactants, silicone-based surfactants and fluorine-based surfactants. As the nonionic surfactant, it is preferred to contain an alcohol surfactant (hereinafter also referred to as "surfactant 1") having an HLB value of less than 10. The HLB value of the surfactant 1 is more preferably less than 4.

[0023] Surfactant 1 is preferably an acetylene glycol surfactant. The acetylene glycol surfactant is a surfactant having a carbon-carbon triple bond in the molecule. Examples of acetylene glycol surfactants include acetylene glycol (having an acetylene bond and two hydroxyl groups in the same molecule) surfactants and surfactants obtained by adding ethylene oxides such as propylene oxide to acetylene glycol. Specifically, examples include compounds represented by the following general formula (1) or (2).

[0024]

[0025] (where R 1 and R 2 Each independently represents an alkyl group having 3 to 9 carbon atoms, and R 3 and R 4 Each independently represents an alkylene group having 1 to 4 carbon atoms, m and n each independently represent an integer greater than 1, and the total of m and n is 2 to 50). Examples of the acetylene glycol surfactant, namely, surfactant 1, include: "SURFYNOL (registered trademark)" series, "OLFINE (registered trademark)" series (all produced by Nissin Chemical Industry Co., Ltd.); and "ACETYLENOL (registered trademark)" series (produced by Kawaken Fine Chemicals Co., Ltd.).

[0026] As the nonionic surfactant, it is preferred to contain a nonionic surfactant having an HLB value of 10 or more (hereinafter also referred to as "surfactant 2"). Surfactant 2 is preferably a silicone-based surfactant, and more preferably a polyalkylene-modified dimethylsiloxane having a polyoxyalkylene structure as a hydrophilic portion and a polydimethylsiloxane structure as a hydrophobic portion.

[0027] The polyoxyalkylene-modified dimethylsiloxane may have a polydimethylsiloxane unit (-(CH3)2SiO 2 / 2 -), may have a polydimethylsiloxane unit on the side chain, or may have a polydimethylsiloxane unit on both the main chain and the side chain. The polyoxyalkylene-modified polydimethylsiloxane is preferably a polyoxyalkylene-modified polydimethylsiloxane containing a dimethylsiloxane unit on the main chain and an oxyalkylene unit on the side chain, or a polyoxyalkylene-modified polydimethylsiloxane containing a dimethylsiloxane unit on the main chain and an oxyalkylene unit at the end of the main chain. The oxyalkylene groups contained in the polyoxyalkylene-modified dimethylsiloxane may be composed of only one type of oxyalkylene groups or may be composed of two or more types of oxyalkylene groups. In the latter case, different types of oxyalkylene groups may be connected randomly or in blocks.

[0028] Surfactant 2 as an organic surfactant includes, for example, "BYK-347", "BYK-349", "BYK-378", "BYK-3450", "BYK-3451", "BYK-3455", "BYK-3456" (produced by BYK Chemical Japan Co., Ltd.), "KF-6011", "KF-6043" (produced by Shin-Etsu Chemical Co., Ltd.). In addition, specific examples of other nonionic surfactants include the "Ftergent" series (produced by Neos Co., Ltd.), the "Surflon" series (produced by AGC Seimi Chemical Co., Ltd.), the "MEGA FACE" series (produced by DIC Corporation), the "Unidyne" series (produced by Daikin Industries, Ltd.), and the "Tergitol" series (produced by The Dow Chemical Company, "Tergitol TMN-100X", etc.).

[0029] The content of the nonionic surfactant is preferably in the range of 1 to 15% by mass, more preferably in the range of 3 to 10% by mass, based on the F particles in the present dispersion. The nonionic surfactant may be used alone or in combination of two or more. In particular, it is preferred that the dispersion contains both the surfactant 1 and the surfactant 2 as nonionic surfactants because the above-mentioned mechanism of action is more likely to be manifested. When the present dispersion contains both the surfactant 1 and the surfactant 2 as nonionic surfactants, the content mass ratio of the surfactant 1 and the surfactant 2 is not particularly limited and can be appropriately set within the range of, for example, 5:95 to 95:5.

[0030] The degree of substitution of the cellulose ether contained in the present dispersion is above 1.4. The degree of substitution of the cellulose ether is preferably above 1.9, more preferably above 2.1. In addition, the degree of substitution of the cellulose ether is preferably below 2.9, more preferably below 2.7. The degree of substitution of the cellulose ether preferably ranges from 1.4 to 2.9, more preferably from 1.9 to 2.9, and further preferably from 1.9 to 2.7. When the degree of substitution of the cellulose ether satisfies the above range, its thickening effect and the interaction with the F particles are balanced through the relationship with the above nonionic surfactant, and the above mechanism of action is easier to manifest, especially when the nonionic surfactant has a hydroxyl group or a polyoxyalkylene group and the cellulose ether has a hydroxyl group, the above mechanism of action is easier to manifest.

[0031] The cellulose ether may, for example, be an alkyl cellulose, a carboxyalkyl cellulose, a hydroxyalkyl cellulose or a hydroxyalkyl alkyl cellulose. Among them, a carboxyalkyl cellulose, a hydroxyalkyl cellulose or a hydroxyalkyl alkyl cellulose is preferred.

[0032] Examples of the carboxyalkyl cellulose include carboxymethyl cellulose, etc. Examples of the hydroxyalkyl cellulose include hydroxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, etc. Examples of the hydroxyalkyl alkyl cellulose include hydroxypropyl methyl cellulose, hydroxyethyl methyl cellulose, hydroxyethyl ethyl cellulose, hydroxyethyl ethyl methyl cellulose, etc. These may be used alone or in combination of two or more. Among them, hydroxyalkyl cellulose or hydroxyalkyl alkyl cellulose is preferred, hydroxyalkyl cellulose is more preferred, and hydroxyethyl cellulose is further preferred.

[0033] The weight average molecular weight of the cellulose ether is preferably 1000 to 10000. The weight average molecular weight can be measured, for example, by gel permeation chromatography (GPC) using a differential refractive index detector. Specific examples of cellulose ether include "SUNROSE (registered trademark)" series (produced by Nippon Paper Industries, Ltd.), "METOLOSE (registered trademark)" series (produced by Shin-Etsu Chemical Co., Ltd.), and "HEC CF grade" (produced by Sumitomo Seika Chemicals, Ltd.).

[0034] The present dispersion may further contain a monohydric alcohol having 1 to 6 carbon atoms. The monohydric alcohol having 1 to 6 carbon atoms is a compound that is liquid at 25°C under atmospheric pressure, preferably a compound having a boiling point of 160°C or less, and more preferably a compound having a boiling point of 120°C or less. In addition, a water-soluble compound having a surface tension of 20 to 30 mN / m is preferred, and preferably forms an azeotrope with water. In addition, "water-soluble" in this specification means that the solubility in water is 100 g / L or more.

[0035] As the monohydric alcohol having 1 to 6 carbon atoms, methanol (23 mN / m), ethanol (23 mN / m), 1-propanol (24 mN / m), 2-propanol (22 mN / m), 1-butanol (25 mN / m), 2-butanol (24 mN / m), isobutanol (23 mN / m), 1-methoxy-2-propanol (26 mN / m), 2-propoxy-ethanol (27 mN / m), 1-propoxy-2-propanol (25 mN / m), and 2-ethoxyethanol (26 mN / m) are more preferred, and ethanol is further preferred. The numerical values ​​in parentheses are the surface tensions of the respective monohydric alcohols. These may be used alone or in combination of two or more. When two or more of the above monohydric alcohols are used, they are preferably compatible with each other.

[0036] In addition to the above-mentioned monohydric alcohol and water, other dispersing media may be used in the present dispersion within the scope that does not impair the effect of the present invention. The other dispersing media are preferably mixed with the above-mentioned monohydric alcohol and water. As other dispersing media, amides such as N-methyl-2-pyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, N,N-dimethylpropionamide, 3-methoxy-N,N-dimethylpropionamide, 3-butoxy-N,N-dimethylpropionamide, N,N-diethylformamide, hexamethylphosphoric triamide, 1,3-dimethyl-2-imidazolidinone, etc.; ketones such as acetone and methyl ethyl ketone.

[0037] The present dispersion may further contain an inorganic filler. In this case, a molded product such as a coating film (polymer layer) formed from the present dispersion is likely to be excellent in electrical properties and low linear expansion. The shape of the inorganic filler can be any of spherical, needle-shaped (fibrous), and plate-shaped. Specifically, it can be spherical, flaky, layered, leaf-shaped, almond-shaped, columnar, cockscomb-shaped, equiaxed, leaf-shaped, mica-shaped, blocky, flat, wedge-shaped, rosette-shaped, mesh-shaped, and prism-shaped. Examples of the inorganic filler include silicon compounds such as quartz powder, silicon dioxide, wollastonite, talc, silicon nitride, silicon carbide, and mica; nitrogen compounds such as boron nitride and aluminum nitride; metal oxides such as aluminum oxide, zinc oxide, titanium oxide, cerium oxide, beryllium oxide, magnesium oxide, nickel oxide, vanadium oxide, copper oxide, iron oxide, and silver oxide; carbon fibers; allotropes of carbon such as graphite, graphene, and carbon nanotubes; and metals such as silver and copper. The inorganic filler may be used alone or in combination of two or more. The D50 of the inorganic filler is preferably 0.1 to 50 μm. The surface of the inorganic filler may be surface treated with a silane coupling agent.

[0038] Preferred specific examples of inorganic fillers include: silica fillers ("admafin (registered trademark)" series (produced by Yaduma Technology Co., Ltd.), "SFP (registered trademark)" series (produced by Denka Co., Ltd.), "E-SPHERES" series (produced by Pacific Cement Co., Ltd.)), zinc oxide fillers ("FINEX (registered trademark)" series (produced by Sakai Chemical Industry Co., Ltd.)), titanium oxide fillers ("TIPAQUE (registered trademark)" series (produced by Takumi Chemical Industry Co., Ltd.)), series (produced by Ishihara Sangyo Co., Ltd.), "JMT (registered trademark)" series (produced by Teika Co., Ltd.), talc fillers ("SG" series (produced by Nippon Talc Co., Ltd.), block talc fillers ("BST" series (produced by Nippon Talc Co., Ltd.), boron nitride fillers ("UP40MF" series, "UP40" series (both produced by Mizushima Iron & Steel Co., Ltd.), "UHP" series (produced by Showa Denko K.K.), "Denka Boron Nitride" series of "GP", "HGP" grades (produced by Denka Co., Ltd.), etc.). When the present dispersion contains an inorganic filler, the content of the inorganic filler in the present dispersion is preferably 1 to 25% by mass.

[0039] The present dispersion may further include other resins different from the polymer F. The other resins may be included in the present dispersion in the form of non-hollow particles, or may be dissolved or dispersed in a liquid dispersion medium (hereinafter also referred to as "liquid dispersion medium") such as water constituting the present dispersion, or a monohydric alcohol having 1 to 6 carbon atoms or other dispersion medium as required. As other resins, polyester resins such as liquid crystalline aromatic polyesters, polyimide resins, polyamideimide resins, epoxy resins, maleimide resins, polyurethane resins, polyphenylene ether resins, polyphenylene ether resins and polyphenylene sulfide resins may be mentioned. As the other resin, an aromatic polymer is preferred, and at least one aromatic imide polymer selected from aromatic polyimide, aromatic polyamic acid, aromatic polyamideimide and aromatic polyamideimide precursor is more preferred. The aromatic polymer is preferably contained in the present dispersion in the form of a varnish dissolved in a liquid dispersion medium.

[0040] Specific examples of aromatic imide polymers include the "UPIA-AT" series (produced by Ube Industries, Ltd.), the "Neopulim (registered trademark)" series (produced by Mitsubishi Gas Chemical Co., Ltd.), the "SPIXAREA (registered trademark)" series (produced by Somaron Co., Ltd.), the "Q-pilon (registered trademark)" series (produced by PI Technology Research Institute), the "WINGO" series (produced by WINGO Technology Co., Ltd.), the "Tohmide (registered trademark)" series (produced by Dick Toka Co., Ltd.), the "KPI-MX" series (produced by Kawamura Sangyo Co., Ltd.), and "HPC-1000" and "HPC-2100D" (both produced by Showa Denko Materials Co., Ltd.). When the present dispersion further contains other resins, the content of the other resins is preferably 1 to 25% by mass based on the F particles.

[0041] The present dispersion may further contain additives such as thixotropy imparting agent, viscosity modifier, defoamer, dehydrating agent, plasticizer, weathering agent, antioxidant, heat stabilizer, lubricant, antistatic agent, brightener, colorant, conductive agent, release agent, flame retardant and the like.

[0042] The present dispersion can be obtained by mixing F particles, a nonionic surfactant, cellulose ether, water, and, if necessary, the above-mentioned monohydric alcohol having 1 to 6 carbon atoms, other dispersion media, inorganic fillers, other resins, additives, and the like. The present dispersion can be obtained by mixing F particles, nonionic surfactant, cellulose ether and water together, or by mixing them one by one, or by making a masterbatch of these components in advance and mixing them with the remaining components. There is no particular limitation on the mixing order, and the mixing method can be one-time mixing or multiple separate mixing.

[0043] For example, from the viewpoint of improving dispersibility, it is preferred to disperse the F particles in a part of water in advance, then sequentially add a nonionic surfactant and cellulose ether and mix, and then add the resulting mixture to the remaining water to obtain the present dispersion. The nonionic surfactant may be added directly or in the form of an aqueous solution. In addition, when both the above-mentioned surfactant 1 and the surfactant 2 are used as the nonionic surfactant, there is no particular restriction on the order of addition, and both may be added in the form of an aqueous solution in which they are dissolved. The cellulose ether may be added in the form of a powder or an aqueous solution thereof, or in the form of a dispersion or a solution in a liquid defoamer or the like. When the monohydric alcohol having 1 to 6 carbon atoms, other dispersion medium, inorganic filler, other resin, additives, etc. are further mixed as necessary, they may be mixed when the F particles and water are mixed or when the mixture is added to water.

[0044] Examples of the mixing device for obtaining the present dispersion include stirring devices equipped with blades such as Henschel mixers, pressure kneaders, Banbury mixers and planetary mixers; pulverizing devices equipped with media such as ball mills, crushers, basket mills, sand mills, sand mills, DYNO mills, DISPERMAT dispersers, SC mills, Spike mills or stirred mills; and dispersing devices equipped with other mechanisms such as microfluidizers, nanometers, Ultimaizer dispersers, ultrasonic homogenizers, dissolvers, high-speed impeller dispersers, thin film gyratory high-speed mixers, rotational revolution stirrers and V-type mixers.

[0045] The content of F particles in the present dispersion is preferably more than 30% by mass, more preferably more than 35% by mass, from the viewpoint of being easy to form a thick layered molded product therefrom and being easy to impart high physical properties to the F polymer in the obtained molded product. The content of F particles is preferably less than 75% by mass, more preferably less than 60% by mass. The content of the nonionic surfactant in the present dispersion is preferably 1 to 15 parts by mass, more preferably 3 to 10 parts by mass, based on 100 parts by mass of the F particles.

[0046] From the viewpoint of improving the fluidity of the present dispersion, the content of cellulose ether in the present dispersion is preferably 0.01% by mass or more, more preferably 0.02% by mass or more, relative to the present dispersion. The content of cellulose ether is preferably 1% by mass or less, preferably 0.1% by mass or less.

[0047] The water content in the present dispersion is preferably 25% by mass or more, more preferably 40% by mass or more. The water content is preferably less than 70% by mass, more preferably 65% ​​by mass or less. In addition, the water content in the present dispersion is preferably 60 to 180% by mass relative to the content of the F particles.

[0048] When the present dispersion contains a monohydric alcohol having 1 to 6 carbon atoms, the content thereof is preferably 0.1% by mass or more, more preferably 1% by mass or more relative to the present dispersion. The content of the monohydric alcohol having 1 to 6 carbon atoms is preferably 10% by mass or less, preferably 5% by mass or less. From the perspective of the dispersion stability of the F particles, it is believed that the monohydric alcohol having 1 to 6 carbon atoms also plays a defoaming role such as a foam suppressing effect or a foam breaking effect even when a large amount of nonionic surfactant is contained.

[0049] The viscosity of the present dispersion is preferably above 10 mPa·s, more preferably above 100 mPa·s. The viscosity of the present dispersion is preferably below 10000 mPa·s, more preferably below 3000 mPa·s. In this case, the present dispersion has excellent coating properties and is easy to form a molded product such as a coating film (polymer layer) with any thickness. In addition, the present dispersion within the viscosity range of this range is easy to highly manifest the physical properties of the F polymer in the molded product formed therefrom. The thixotropic ratio of the present dispersion is preferably 1.0 to 3.0. In this case, the present dispersion has excellent coating properties and homogeneity, and a denser molded product can be easily produced.

[0050] From the viewpoint of improving long-term storage properties, the pH of the present dispersion is more preferably 8 to 10. The pH of the present dispersion can be adjusted by a pH adjuster (amine, ammonia, citric acid, etc.) or a pH buffer (tris(hydroxymethyl)aminomethane, ethylenediaminetetraacetic acid, ammonium bicarbonate, ammonium carbonate, ammonium acetate, etc.).

[0051] The dielectric constant of the molded product formed from the present dispersion is preferably 2.4 or less, more preferably 2.0 or less. In addition, the dielectric constant is preferably greater than 1.0. The dielectric loss tangent of the molded product is preferably 0.0022 or less, more preferably 0.0020 or less. In addition, the dielectric loss tangent is preferably greater than 0.0010. The thermal conductivity of the molded product is preferably 1 W / m·K or more, more preferably 3 W / m·K or more.

[0052] The present dispersion is subjected to a forming method such as extrusion into a sheet, and a shaped article such as a sheet containing the F polymer can be formed. The extruded sheet can be further cast by pressure forming, calendaring, etc. The sheet is preferably further heated to remove the liquid dispersion medium and calender the F polymer.

[0053] The thickness of the sheet formed from the present dispersion is preferably 1 to 1000 μm. The preferred ranges of the dielectric constant, dielectric loss tangent and thermal conductivity of the sheet are the same as those of the above-mentioned molded product, respectively. The thermal conductivity of the sheet refers to the thermal conductivity in the in-plane direction of the sheet. The linear expansion coefficient of the sheet is preferably 100 ppm / °C or less, more preferably 80 ppm / °C or less. The lower limit of the linear expansion coefficient of the sheet is 30 ppm / °C. The linear expansion coefficient refers to a value obtained by measuring the linear expansion coefficient of a test piece in the range of 25°C or more and 260°C or less according to the measurement method specified in JIS C 6471:1995.

[0054] The sheet is laminated on a substrate to form a laminate. Examples of a method for producing the laminate include a method of extruding the present dispersion onto the substrate, a method of thermocompression bonding the sheet and the substrate, and the like. Examples of the substrate include: metal substrates such as metal foils of copper, nickel, aluminum, titanium, alloys thereof, etc.; films of heat-resistant resins such as polyimide, polyamide, polyetheramide, polyphenylene sulfide, polyallyl ether ketone, polyamideimide, liquid crystalline polyester, tetrafluoroethylene polymers, etc.; prepreg substrates (precursors of fiber-reinforced resin substrates), ceramic substrates such as silicon carbide, aluminum nitride, silicon nitride, etc.; and glass substrates.

[0055] The shape of the substrate may be a flat surface, a curved surface, or a concave-convex shape. The substrate may also be in the form of a foil, a plate, a film, or a fiber. The ten-point average roughness of the substrate surface is preferably 0.01 to 0.05 μm. The surface of the substrate can be surface treated with a silane coupling agent or plasma treated. As the silane coupling agent, preferably a silane coupling agent having a functional group such as 3-aminopropyltriethoxysilane, vinyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-glycidyloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-isocyanatepropyltriethoxysilane, etc. The peel strength between the sheet and the substrate is preferably 10 to 100 N / cm.

[0056] Furthermore, the present dispersion is placed on the surface of a substrate and heated to form a polymer layer containing the F polymer (hereinafter also referred to as "F layer"), thereby obtaining a laminate having a substrate layer composed of a substrate and an F layer in this order. The F layer is preferably formed by placing the present dispersion on the surface of the substrate, heating to remove the liquid dispersion medium, and further heating to calcine the polymer F. By separating the substrate from the laminate, a sheet containing the polymer F can be obtained. As the substrate, there may be mentioned the same substrates as those which may be laminated on the above-mentioned sheet, and preferred aspects thereof are also the same.

[0057] The method for preparing the present dispersion may, for example, be a coating method, a droplet discharging method or a dipping method, and preferably a roll coating method, a knife coating method, a bar coating method, a die coating method or a spraying method. The heating for removing the liquid dispersion medium is preferably carried out at 100 to 200° C. for 0.1 to 30 minutes. During the heating at this time, the liquid dispersion medium does not need to be completely removed, as long as it is removed to the extent that the layer formed by the accumulation of F particles can maintain a self-supporting film. In addition, air can be blown during heating to promote the removal of the liquid dispersion medium by air drying.

[0058] The heating for calcining the F polymer is preferably performed at a temperature equal to or higher than the melting temperature of the F polymer, more preferably at 360 to 400° C. for 0.1 to 30 minutes. As the heating device in each heating step, an oven and a ventilated drying furnace can be mentioned. The heat source in the device can be a contact heat source (hot air, a heating plate, etc.) or a non-contact heat source (infrared rays, etc.). In addition, each heating step may be carried out under normal pressure or under reduced pressure. In addition, the atmosphere in each heating step may be any of an air atmosphere and an inert gas (helium, neon, argon, nitrogen, etc.) atmosphere.

[0059] The F layer is formed by the arrangement and heating steps of the present dispersion. These steps may be performed one by one or more times. For example, the present dispersion may be arranged on the surface of the substrate and heated to form the F layer, and the present dispersion may be further arranged on the surface of the F layer and heated to form the second F layer. In addition, the present dispersion may be further arranged on the surface of the substrate and heated to remove the liquid dispersion medium to form the F layer. The present dispersion may be disposed on only one surface of the substrate or on both surfaces of the substrate. In the former case, a laminate having a substrate layer and an F layer on one surface of the substrate layer may be obtained, and in the latter case, a laminate having an F layer on both surfaces of the substrate layer and the substrate layer may be obtained. The thickness of the F layer varies depending on the application of the laminate, but is preferably in the range of 1 to 1000 μm.

[0060] Preferred specific examples of the laminate include a metal foil and a metal-clad laminate having an F layer on at least one surface of the metal foil, a polyimide film, and a multilayer film having an F layer on both surfaces of the polyimide film. The preferred ranges of the thickness, dielectric constant, dielectric loss tangent, thermal conductivity, linear expansion coefficient, and peel strength between the F layer and the substrate layer are the same as the preferred ranges of the thickness, dielectric constant, dielectric loss tangent, thermal conductivity, linear expansion coefficient, and peel strength between the sheet formed from the above-mentioned dispersion.

[0061] The present dispersion can be used as a material for imparting insulation, heat resistance, corrosion resistance, chemical resistance, water resistance, impact resistance, and thermal conductivity. Specifically, the dispersion can be used for printed wiring boards, thermal interface materials, substrates for power modules, coils used in power equipment such as motors, vehicle engines, heat exchangers, vials, syringes (Syringe), ampoules, medical wires, secondary batteries such as lithium-ion secondary batteries, primary batteries such as lithium batteries, free radical batteries, solar cells, fuel cells, lithium-ion capacitors, hybrid capacitors, capacitors (capacitors), capacitors (condensers) (aluminum electrolytic capacitors, tantalum electrolytic capacitors, etc.), electrochromic elements, electrochemical switching elements, electrode adhesives, electrode separators and electrodes (positive and negative electrodes). In addition, the dispersion can also be used as an adhesive for bonding parts. Specifically, the dispersion can be used for bonding ceramic parts, bonding metal parts, bonding electronic parts such as IC chips, resistors, capacitors, etc. on substrates of semiconductor elements or module parts, bonding circuit substrates and heat sinks, and bonding LED chips on substrates.

[0062] The molded products and laminates formed from the present dispersion can be used as antenna parts, printed circuit boards, aircraft parts, automobile parts, sports equipment, food industry products, heat dissipation parts, and the like. Specifically, it can be used as wire coating materials (wires for aircraft, rectangular wires, FFC (Flexible flat cable), etc.), enameled wire coating materials used in motors of electric vehicles, etc., power generation coating materials, electrical insulating tapes, insulating tapes for oil drilling, oil pipelines, hydrogen tanks, printed circuit board materials, separation membranes (precision filtration membranes, ultrafiltration membranes, reverse osmosis membranes, ion exchange membranes, dialysis membranes, gas separation membranes, etc.), electrode adhesives (for lithium secondary batteries, fuel cells, etc.), fuel cell carrier membranes, tape substrate films for semiconductor manufacturing processes (dicing tapes, pick-up tapes, etc.), semiconductor molding release films, liquid crystal antennas, reflectors, transmission lines, COF (Chip on Film) film), electrostatic chucks for semiconductor manufacturing processes, electrostatic chucks for display manufacturing processes, copy rollers, covers for furniture, automobile dashboards, home appliances, etc., sliding parts (load bearings, yaw bearings, sliding shafts, valves, bearings, bushings, seals, thrust washers, wear rings, pistons, slide switches, gears, cams, belt conveyors, food conveyor belts), tension ropes, wear pads, wear strips, tube lights, test sockets, wafer guides, wear parts of centrifugal pumps, chemical and water supply pumps, tools (shovels, files, chisels, saws, etc.), boilers, hoppers, pipes, ovens Boxes, baking molds, chutes, racket strings, molds, toilets, container covering materials, heat dissipation substrates for power devices, heat dissipation components of wireless communication devices, transistors, thyristors, rectifiers, transformers, power MOSFETs, CPUs, heat sinks, metal heat dissipation plates, blades of windmills or wind power generation equipment or aircraft, computer or display frames, electronic device materials, automotive interior and exterior trim, processing machines or vacuum furnaces that perform heat treatment under low oxygen, sealing materials for plasma processing equipment, heat dissipation components in processing units such as sputtering or various dry etching equipment, and electromagnetic wave shielding bodies.

[0063] Formed products such as sheets and laminates formed from the present dispersion can be used as electronic substrate materials such as flexible printed circuit boards and rigid printed circuit boards, protective films, or heat dissipation substrates, particularly heat dissipation substrates for automobiles. Example

[0064] The present invention is described in detail below by way of examples, but the present invention is not limited thereto. 1. Preparation of Ingredients [F polymer] F particles 1: containing 97.9 mol% TFE units, 0.1 mol% NAH units and 2.0 mol% PPVE units, and the main chain carbon number is 1×10 6 Particles of tetrafluoroethylene polymer (melting temperature: 300°C) containing 1000 carbonyl groups (D50: 2.0 μm, specific surface area: 7 m 2 / g) F particles 2: containing 97.5 mol% TFE units and 2.5 mol% PPVE units and the main chain carbon number is 1×10 6 Particles of tetrafluoroethylene polymer (melting temperature: 300°C) having 50 carbonyl groups (D50: 2.2 μm, specific surface area: 6 m 2 / g) [Nonionic surfactant] Surfactant 1: a nonionic alcohol surfactant having one acetylene group and two hydroxyl groups and an HLB value of 3 ("SURFYNOL DF-110D" (trade name, produced by Nissin Chemical Industry Co., Ltd.) Surfactant 2: A nonionic silicone surfactant having a polysiloxane chain on the main chain and a polyoxyethylene group on the side chain, with an HLB value of 13 [Cellulose ether] Cellulose ether 1: Hydroxyethyl cellulose with a degree of substitution of 2.4 Cellulose ether 2: Hydroxyethyl cellulose with a degree of substitution of 1.5 Cellulose ether 3: Hydroxyethyl cellulose with a degree of substitution of 1.3

[0065] 2. Example of Preparation of Aqueous Dispersion [Example 1] F particles 1, surfactant 1, surfactant 2, cellulose ether 1 and water were stirred at 2000 rpm for 10 minutes using a rotary revolution stirrer (Shinki Co., Ltd., trade name "Awatori Rentaro (registered trademark) ARE-310") to obtain a dispersion 1 (viscosity: 1000 mPa·s) containing F particles 1 (46.5 parts by mass), surfactant 1 (0.9 parts by mass), surfactant 2 (2.3 parts by mass), cellulose ether 1 (0.3 parts by mass) and water (50.0 parts by mass).

[0066] [Example 2] A dispersion 2 containing F particles 1 (46.5 parts by mass), surfactant 1 (3.2 parts by mass), cellulose ether 1 (0.3 parts by mass) and water (50.0 parts by mass) was obtained in the same manner as in Example 1 except that surfactant 2 was not added. [Example 3] A dispersion 3 containing F particles 1 (46.5 parts by mass), surfactant 2 (3.2 parts by mass), cellulose ether 1 (0.3 parts by mass) and water (50.0 parts by mass) was obtained in the same manner as in Example 1 except that surfactant 1 was not added.

[0067] [Example 4] A dispersion 4 containing F particles 1 (46.5 parts by mass), surfactant 1 (0.9 parts by mass), surfactant 2 (2.3 parts by mass), cellulose ether 2 (0.3 parts by mass) and water (50.0 parts by mass) was obtained in the same manner as in Example 1 except that cellulose ether 2 was used instead of cellulose ether 1. [Example 5] A dispersion 5 containing F particles 2 (46.5 parts by mass), surfactant 1 (0.9 parts by mass), surfactant 2 (2.3 parts by mass), cellulose ether 1 (0.3 parts by mass) and water (50.0 parts by mass) was obtained in the same manner as in Example 1, except that F particles 2 were used instead of F particles 1. [Example 6] A dispersion 6 containing F particles 1 (46.5 parts by mass), surfactant 1 (0.9 parts by mass), surfactant 2 (2.3 parts by mass), cellulose ether 3 (0.3 parts by mass) and water (50.0 parts by mass) was obtained in the same manner as in Example 1 except that cellulose ether 3 was used instead of cellulose ether 1.

[0068] 3. Evaluation 3-1. Foaming property and dispersion stability of dispersion 50 ml of each dispersion was placed in a 100 ml transparent container, and the transparent container was shaken up and down 10 times and then left to stand for 10 minutes. The foaming state after 10 minutes was visually confirmed, and the presence of component sedimentation after 7 days of storage was visually confirmed, and evaluated according to the following criteria. <Evaluation Criteria> A: The foam disappears just by standing still, and the ingredients do not settle after storage, and are well dispersed B1: The foam disappears after just standing, and the components partially settle after storage, making it easy to redisperse B2: The foaming can be removed by decompression degassing after standing. In addition, the components do not settle after storage and are well dispersed. C: Foaming, difficult to defoam even after standing, components settle after storage

[0069] 3-2. Evaluation of fluidity of dispersion and production of laminate The surface of the substrate (polyimide film ("FG-100" produced by PI Advanced Materials: thickness 25 μm) was coated with each dispersion by a small-diameter gravure reverse method to form a coating layer, and then heated and sintered to obtain a laminate having a polymer layer (thickness 25 μm) on both sides of the substrate. At this time, the surface of the coating layer was visually observed for the presence of bubbles and streaks, and evaluated according to the following criteria. <Evaluation criteria for coating surface> A: No bubbles at all, smooth surface with no visible streaks B: No visible bubbles, smooth surface but irregular ribs can be observed C: Visible blistering and visible striae The above results are summarized in Table 1.

[0070] Table 1 Dispersion No. 1 2 3 4 5 6 Dispersion stability A B1 B2 B2 B2 C Liquidity A A B B A C Industrial Applicability

[0071] The dispersion of the present invention is excellent in dispersion stability and handling properties and can form a molded product such as a coating film (polymer layer) that highly exhibits the physical properties of the F polymer, especially excellent in surface appearance.

[0072] In addition, the entire contents of the specification, claims, and abstract of Japanese Patent Application No. 2022-094392 filed on Jun. 10, 2022 are cited herein and are incorporated herein as a disclosure of the specification of the present invention.

Claims

1. A dispersion comprising particles of a tetrafluoroethylene polymer, a nonionic surfactant, a cellulose ether having a degree of substitution of 1.4 or more, and water.

2. The dispersion according to claim 1, wherein The average particle size of the tetrafluoroethylene polymer particles is 1 μm or more and less than 10 μm, and the specific surface area is 1 to 25 m 2 / g.

3. The dispersion according to claim 1, wherein The content of the tetrafluoroethylene polymer particles exceeds 30% by mass.

4. The dispersion according to claim 1, wherein The tetrafluoroethylene polymer is a tetrafluoroethylene polymer having a carbonyl group.

5. The dispersion according to claim 4, wherein The main chain carbon number of tetrafluoroethylene polymer is 1×10 6 There are 100 to 3000 carbonyl-containing groups.

6. The dispersion according to claim 1, wherein The nonionic surfactant includes an alcohol surfactant having an HLB value of less than 10.

7. The dispersion according to claim 1, wherein The nonionic surfactant contains a nonionic surfactant having an HLB value of 10 or more.

8. The dispersion according to claim 1, wherein The nonionic surfactant includes an alcohol surfactant having an HLB value of less than 10 and a silicone surfactant having an HLB value of 10 or more.

9. The dispersion according to claim 1, wherein The content of the nonionic surfactant is 1 to 15% by mass relative to the content of the particles.

10. The dispersion according to claim 1, wherein The degree of substitution of the cellulose ether is 1.9 to 2.

9.

11. The dispersion according to claim 1, wherein The cellulose ether is carboxyalkyl cellulose, hydroxyalkyl cellulose or hydroxyalkyl alkyl cellulose.

12. The dispersion according to claim 1, wherein The cellulose ether is hydroxyalkyl cellulose or hydroxyalkyl alkyl cellulose.

13. The dispersion according to claim 1, wherein It also contains monohydric alcohols having 1 to 6 carbon atoms.

14. The dispersion according to claim 1, wherein The invention further contains at least one selected from aromatic polymers and inorganic fillers.

15. A method for producing a laminate, wherein: The dispersion according to any one of claims 1 to 14 is placed on the surface of a substrate and heated to form a polymer layer containing the tetrafluoroethylene polymer, thereby obtaining a laminate having a substrate layer composed of the substrate and the polymer layer in this order.

Citation Information

Patent Citations

  • Fluororesin water dispersion

    JP2019052211A

  • Hub bracket structure

    JP2022094392A

  • Liquid composition, and method for manufacturing film and layered body using same

    WO2018016644A1

  • Fluororesin composition, fluororesin sheet, multilayer body and substrate for circuits

    WO2020145133A1

  • Composition for coating, and coated article

    WO2022054762A1